Proteomic identification of a two-component regulatory system in Pseudoalteromonas haloplanktis TAC125 - PAPA, Rosanna; S. Glagla; A. Danchin; T. Schweder; G. Marino; A. Duilio (Extremophiles, 2006)
The capability of microorganisms to utilize different carbohydrates as energy source reflects the availability of these substrates in their habitat. Investigation of the proteins involved in carbohydrate usage, in parallel with analysis of their expression, is then likely to provide information on the interaction between microorganisms and their ecosystem. We analysed the growth behaviour of the marine Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 in the presence and in the absence of different carbon source. A marked increase in the optical density was detected when L-malate was added to the growth medium. Bacterial proteins differently expressed in the presence of L-malate were identified by proteomic profiling experiments. On the basis of their relative increase, six proteins were selected for further analyses. Among these, the expression of a putative outer membrane porin was demonstrated to be heavily induced by L-malate. The presence of a functionally active two-component regulatory system very likely controlled by L-malate was found in the upstream region of the porin gene. A non functional genomic porin mutant was then constructed showing a direct involvement of the protein in the uptake of L-malate. To the best of our knowledge, the occurrence of such a regulatory system has never been reported in Pseudoalteromonads so far and might constitute a key step in the development of an effective inducible cold expression system.